The subject in posthumanist theory: Retained rather than dethroned - Andersson, Ingrid (Educational philosophy and theory, 2022)
The aim of this paper is to sketch a conception of a posthuman subject in which we can recognize a cognitive dimension. Through Hayles's widened notion of cognition, I argue that we can retain the interpreting subject within posthumanism and thereby view it as entrenched in the surrounding world. Nonconscious- and conscious cognition, which are the terms that Hayles utilizes, shows how both non-human cognizing systems and the human subject widens while remaining level specific. The text concludes with a discussion of how my alternative has implications for methods of inquiry.